Temperature‐dependent self‐assembly and rheological behavior of a thermoreversible pmma–PnBA–PMMA triblock copolymer gel. Issue 11 (25th March 2017) - Zabet, Mahla; Mishra, Satish; Boy, Ramiz; Walters, Keisha B.; Naskar, Amit K.; Kundu, Santanu
ABSTRACT: Self‐assembly and mechanical properties of triblock copolymers in a mid‐block selective solvent are of interest in many applications. Herein, we report physical assembly of an ABA triblock copolymer, [PMMA–P n BA–PMMA] in two different mid‐block selective solvents, n ‐butanol and 2‐ethyl‐1‐hexanol. Gel formation resulting from end‐block associations and the corresponding changes in mechanical properties have been investigated over a temperature range of −80 °C to 60 °C, from near the solvent melting points to above the gelation temperature. Shear‐rheometry, thermal analysis, and small‐angle neutron scattering data reveal formation and transition of structure in these systems from a liquid state to a gel state to a percolated cluster network with decrease in temperature. The aggregated PMMA end‐blocks display a glass transition temperature. Our results provide new understanding into the structural changes of a self‐assembled triblock copolymer gel over a large length scale and wide temperature range. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2017, 55, 877–887 Abstract : The self‐assembly, mechanical, and thermal properties of a thermoreversible gel consisting of PMMA–P n BA–PMMA in two mid‐block selective solvents, butanol and 2‐ethyl‐1‐hexanol, are investigated over a wide temperature range. The rheological and small angle neutron scattering results capture multiple transitions related to the structure formation in these gels with decreasing temperature.